1872 Conn. Pub. Acts 108 - (:unkn) unknown (My University, 1872)
An Act in Addition to an Act for the Preservation of Game, chap. 115, § 2: Prohibited killing any wild duck, goose, or brant with any instrument known as a punt gun or swivel, or any other such guns as are habitually raised at arms' length and fired from the shoulder. Also prohibited attempt to capture said animals with said instruments, or any other instrument or gun other than such guns aforesaid.
Keywords: HUNTING REGULATION